Efectos de actividades de indagación científica en el rendimiento escolar en ciencia y tecnología en niños de cinco años de la institución educativa inicial N°390 Cochiquinas 2024 - Vela Cruz, Matilde (2025)
The purpose of this research is to determine the effect of scientific inquiry activities on school performance in science and technology in five-year-old children of the Initial Educational Institution N°390 Cochiquina 2024. This study has a quantitative approach with a quasi-experimental design. , the population under study is made up of all five-year-old children from the Initial Educational Institution No. 390 Cochiquina 2024, with a total of 49 children, 24 control group and 25 experimental group. For data collection, the observation technique has been used, using an observation guide as an instrument. Regarding the validity of the instrument, these were evaluated by three experts with extensive experience in the area, guaranteeing that the categories and behaviors identified are relevant and appropriate. The post intervention results showed a significant difference in the performance of both groups. The experimental group reached a mean of 37.04, compared to 22.04 for the control group, using the Student t test for independent samples, showed that the p value was less than 0.01, which allowed us to reject the null hypothesis (Ho) and accept the hypothesis alternative (Ha), concluding that the application of scientific inquiry activities generates significant effects on children's academic performance in science and technology